The Influence of Auditor Competence and Independence on Internal Audit Quality: The Mediating Role of Risk-Based Audit - Suhidayat, Tatang; Evianti, Dessy; Yusuf, Muhammad (Maksi, 2024)
This study aims to analyze the influence of auditor competence and independence on internal audit quality, with risk-based audit as a mediating variable. The research employs a descriptive quantitative method with a population of internal auditors from rural banks (BPR) in West Java. The sample consists of 47 auditors selected using purposive sampling technique. Data processing is performed using Smart PLS 4. The hypothesis testing results indicate that only auditor competence has a significant effect on internal audit quality. Meanwhile, auditor independence does not show a significant effect on internal audit quality, nor does the mediation effect of risk-based audit between auditor competence and independence on internal audit quality. These findings suggest that auditor competence is a key factor in enhancing internal audit quality. This study provides important contributions to the management of internal audits in rural banks, particularly in West Java, by emphasizing the importance of improving auditor competence to achieve better internal audit quality.